Dialogic Organization Development: The Theory and Practice of Transformational Change - and Bushe, Gervase R. (EDS Publications Ltd., 2015)
Dialogic Organization Development is a compelling alternative to the classical action research approach to planned change. Organizations are seen as fluid,socially constructed realities that are continuously created through conversations and images change happens when those conversations and images change. Leaders and consultants can help foster, support, or accelerate the emergence of transformational possibilities by encouraging disruptions to taken-for-granted ways of thinking and acting and the use of generative images to stimulate new organizational conversations and narratives. Dialogic OD is a different mindset, but it s also the previously unrecognized underpinning of such diverse change methods as Appreciative Inquiry, the Art of Convening, Future Search, and many more.